2022
DOI: 10.1213/ane.0000000000005856
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Face of Cystic Fibrosis: An Update for Anesthesiologists

Abstract: Cystic fibrosis (CF) is the most common fatal genetic disease in North America. While CF is more common among Whites, it is increasingly being recognized in other races and ethnicities. Although there is no cure, life expectancy has steadily improved, with the median survival exceeding 46 years in the United States. There are now more adults than children with CF in the United States. CF is caused by mutations in a gene that encodes the cystic fibrosis transmembrane conductance regulator (CFTR) protein, expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 114 publications
(206 reference statements)
0
4
0
Order By: Relevance
“…We appreciate the comments from Nause-Osthoff et al 1 regarding our recent article on the perioperative management of patients with cystic fibrosis that was published in Anesthesia and Analgesia . 2 We agree with them that propofol is superior to volatile anesthetics at blunting airway reflexes, and therefore, propofol is commonly used in patients with cystic fibrosis for induction, maintenance of general anesthesia, or to supplement a general anesthetic with volatile agents for short procedures, such as bronchoscopy, central venous access, sinus surgery, etc. We also agree that desflurane would be a poor choice as it has been shown to cause bronchoconstriction and increase airway resistance in children with bronchial hyperreactivity, such as asthma, recent upper respiratory infections, and cystic fibrosis.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…We appreciate the comments from Nause-Osthoff et al 1 regarding our recent article on the perioperative management of patients with cystic fibrosis that was published in Anesthesia and Analgesia . 2 We agree with them that propofol is superior to volatile anesthetics at blunting airway reflexes, and therefore, propofol is commonly used in patients with cystic fibrosis for induction, maintenance of general anesthesia, or to supplement a general anesthetic with volatile agents for short procedures, such as bronchoscopy, central venous access, sinus surgery, etc. We also agree that desflurane would be a poor choice as it has been shown to cause bronchoconstriction and increase airway resistance in children with bronchial hyperreactivity, such as asthma, recent upper respiratory infections, and cystic fibrosis.…”
mentioning
confidence: 67%
“…As mentioned in our article, we recommend humidification of airway gases, chest physiotherapy, lung recruitment maneuvers, use of bronchodilators if necessary, and suctioning of the endotracheal tube to mobilize secretions and avoid atelectasis. 2…”
mentioning
confidence: 99%
“…A prospective randomized study by Ledowski et al 3 examined the impacts of anesthetics on bronchial mucus transport velocity in 22 patients undergoing elective general anesthesia and found that patients receiving propofol and remifentanil had significantly less impairment of bronchociliary clearance compared to those receiving sevoflurane and remifentanil. Given that the cornerstone of treatment of CF-associated lung disease is mobilization of secretions and aggressive pulmonary clearance, 1 impairment of bronchociliary clearance may be more important for the patient’s overall health than any immediate intraoperative effect, though this remains unstudied. Of note, ketamine and remifentanil may also reduce mucociliary clearance, while morphine does not.…”
Section: To the Editormentioning
confidence: 99%
“…We were pleased to read the excellent article by Lee et al 1 describing the advances in epidemiology, diagnosis, and management of cystic fibrosis (CF). While there were many important recommendations regarding the perioperative optimization of these patients, there was one that requires further clarification.…”
Section: To the Editormentioning
confidence: 99%